Species-Dependent Metabolic Response to Lipid Mixtures in Wine Yeasts - Mbuyane, Lethiwe L.; Bauer, Florian F.; Bloem, Audrey; Camarasa, Carole; Ortiz-Julien, Anne; Divol, Benoit (Frontiers in Microbiology, 2022)
Lipids are essential energy storage compounds and are the core structural elements of all biological membranes. During wine alcoholic fermentation, the ability of yeasts to adjust the lipid composition of the plasma membrane partly determines their ability to cope with various fermentation-related stresses, including elevated levels of ethanol and the presence of weak acids. In addition, the lipid composition of grape juice also impacts the production of many wine-relevant aromatic compounds. Several studies have evaluated the impact of lipids and of their metabolism on fermentation performance and aroma production in the dominant wine yeast Saccharomyces cerevisiae, but limited information is available on other yeast species. Thus, the aim of this study was to evaluate the influence of specific fatty acid and sterol mixtures on various non-Saccharomyces yeast fermentation rates and the production of primary fermentation metabolites. The data show that the response to different lipid mixtures is species-dependent. For Metschnikowia pulcherrima, an increase in carbon dioxide production was observed in media enriched with unsaturated fatty acids whereas Kluyveromyces marxianus fermented better in synthetic media containing a higher concentration of polyunsaturated fatty acids than monounsaturated fatty acids. Torulaspora delbrueckii fermentation rate increased in media supplemented with lipids present at an equimolar concentration. The data indicate that these different responses may be linked to variations in the lipid profile of these yeasts and divergent metabolic activities, in particular the regulation of acetyl-CoA metabolism. Finally, the results suggest that the yeast metabolic footprint and ultimately the wine organoleptic properties could be optimized via species-specific lipid adjustments.